Loss of retinitis pigmentosa 2 (RP2) protein affects cone photoreceptor sensory cilium elongation in mice. Issue 9 (14th October 2015) - Li, Linjing; Rao, Kollu Nageswara; Zheng‐Le, Yun; Hurd, Toby W.; Lillo, Concepción; Khanna, Hemant
Abstract : Degeneration of photoreceptors (rods and cones) results in blindness. As we rely almost entirely on our daytime vision mediated by the cones, it is the loss of these photoreceptors that results in legal blindness and poor quality of life. Cone dysfunction is usually observed due to two mechanisms: noncell‐autonomous due to the secondary effect of rod death if the causative gene is specifically expressed in rods and cell autonomous, if the mutation is in a cone‐specific gene. However, it is difficult to dissect cone autonomous effect of mutations in the genes that are expressed in both rods and cones. Here we report a property of murine cone photoreceptors, which is a cone‐autonomous effect of the genetic perturbation of the retinitis pigmentosa 2 ( Rp2 ) gene mutated in human X‐linked RP. Constitutive loss of Rp2 results in abnormal extension of the cone outer segment (COS). This effect is phenocopied when the Rp2 gene is ablated specifically in cones but not when ablated in rods. Furthermore, the elongated COS exhibits abnormal ultrastructure with disorganized lamellae. Additionally, elongation of both the outer segment membrane and the microtubule cytoskeleton was observed in the absence of RP2. Taken together, our studies identify a cone morphological defect in retinal degeneration due to ablation of RP2 and will assist in understanding cone‐autonomous responses during disease and develop targeted therapies. © 2015 Wiley Periodicals, Inc.